2021
DOI: 10.3390/vaccines9101172
|View full text |Cite
|
Sign up to set email alerts
|

Public Willingness and Determinants of COVID-19 Vaccination at the Initial Stage of Mass Vaccination in China

Abstract: The present study assessed the willingness of the general population to receive COVID-19 vaccines and identified factors that influence vaccine hesitancy and resistance. A national online survey was conducted from 29 January 2021 to 26 April 2021 in China. Multinomial logistic regression analyses were conducted to identify factors that influence vaccine hesitancy and resistance. Of the 34,041 participants surveyed, 18,810 (55.3%) were willing to get vaccinated, 13,736 (40.3%) were hesitant, and 1495 (4.4%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
29
3
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 33 publications
9
29
3
3
Order By: Relevance
“…A total of 250 respondents who were younger than 18 years were also excluded because obtaining online informed consent from their parents may not be realistic. Finally, a total of 34,041 respondents were included, with a response rate of 51.6% and an effective response rate of 99.3% [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 250 respondents who were younger than 18 years were also excluded because obtaining online informed consent from their parents may not be realistic. Finally, a total of 34,041 respondents were included, with a response rate of 51.6% and an effective response rate of 99.3% [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…PHQ-9, GAD-7 and ISI inquires about depression, anxiety and insomnia symptoms in the past 2 weeks while PCL-5 inquires about PTSD symptoms in the recent month. The cutoff scores were 5, 5, 8, and 33 for detecting depression, anxiety, insomnia and posttraumatic stress disorder (PTSD) symptoms, respectively, according to a previous study [ 7 , 19 , 20 ]. Scores of participants greater than cutoff threshold indicate potential mental health symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…As the pandemic progressed, people reporting their intention to be vaccinated against COVID-19 varied [4,6,7,[13][14][15][16][17][18][19]. However, most studies on COVID-19 vaccine acceptance were conducted before the first vaccine's approval or vaccination program rollout.…”
Section: Introductionmentioning
confidence: 99%
“…Several cross-sectional studies have since explored COVID-19 vaccine acceptance and hesitancy and their determinants after the respective countries' vaccination program implementation, namely in European countries [2], such as the United Kingdom [15,16,20,21], Germany [15,22], Denmark [15,23], France [15], Hungary [15], Sweden [15], Italy [15], Norway [21], Poland [24], the Netherlands [25], Spain [26] and Greece [27]. Additional studies were also conducted in Saudi Arabia [28], the United States of America [13,17,21,29], South Africa [21,30], Jordan [31], Israel [32], Chile [33], China [18,21,34,35], Japan [21,36] and Australia [21], among others [21]. These studies have not only reported variation in the refusal rate of COVID-19 vaccination over sequential waves [13][14][15]18], but also on the characteristics of the individuals that reported hesitancy in getting vaccinated [13,14,18] and on the reasons behind this refusal…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation